2010
DOI: 10.1016/j.resuscitation.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transthoracic impedance during real cardiac arrest defibrillation attempts in older children and adolescents: Are stacked-shocks appropriate?

Abstract: Background In 2005, the AHA changed the treatment recommendation for shockable rhythms from 3 transthoracic stacked-shocks to a single shock followed by immediate chest compressions. The stacked-shock recommendation was based on low first-shock efficacy of monophasic waveforms and the theoretical decrease in transthoracic impedance (TTI) following each shock. The objective of this study was to characterize TTI following biphasic defibrillation attempts in children ≥8 yrs during cardiac arrest to assess whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The 200, 200 and 360 J sequence, therefore, was thought to result in an increased transmyocardial current with each shock. Studies in both adults [13,20] and children [21] using biphasic waveforms have shown that the magnitude of any decrease in TTI with sequential shocks is so minimal as to make no significant clinical difference.…”
Section: Changes In Transthoracic Impedance With Sequential Shocksmentioning
confidence: 99%
“…The 200, 200 and 360 J sequence, therefore, was thought to result in an increased transmyocardial current with each shock. Studies in both adults [13,20] and children [21] using biphasic waveforms have shown that the magnitude of any decrease in TTI with sequential shocks is so minimal as to make no significant clinical difference.…”
Section: Changes In Transthoracic Impedance With Sequential Shocksmentioning
confidence: 99%